Niche-mediated bacterial community composition in continental glacier alluvial valleys under cold and arid environments - Chen, Xianke; Qi, Xiangning; Ren, Ge; Chang, Ruiying; Qin, Xiang; Liu, Guohua; Zhuang, Guoqiang; Ma, Anzhou (Frontiers in Microbiology, 2023)
Introduction Bacteria are an essential component of glacier-fed ecosystems and play a dominant role in driving elemental cycling in the hydrosphere and pedosphere. However, studies of bacterial community composition mechanisms and their potential ecological functions from the alluvial valley of mountain glaciers are extremely scarce under cold and arid environments. Methods Here, we analyzed the effects of major physicochemical parameters related to soil on the bacterial community compositions in an alluvial valley of the Laohugou Glacier No. 12 from the perspective of core, other, and unique taxa and explored their functional composition characteristics. Results and discussion The different characteristics of core, other, and unique taxa highlighted the conservation and difference in bacterial community composition. The bacterial community structure of the glacial alluvial valley was mainly affected by the above sea level, soil organic carbon, and water holding capacity. In addition, the most common and active carbon metabolic pathways and their spatial distribution patterns along the glacial alluvial valley were revealed by FAPTOTAX. Collectively, this study provides new insights into the comprehensive assessment of glacier-fed ecosystems in glacial meltwater ceasing or glacier disappearance.